Designing a mini model of wind turbine blade base on horizontal axis wind turbine model - Mohd Izzat Ibrahim
This final year project is about to design a mini model of wind turbine blades based on horizontal axis wind turbine model and to build a mini model of horizontal axis wind turbine that can produce electricity.